(untitled) (Rajarshi Janak University Research Journal, 2024)
Raja Rao’s novel The Serpent and the Rope (1960) delineates the theme of soul’s progress from avidya to vidya (ignorance to knowledge) and a man’s quest for the Absolute. Through the character portrayal of Ramaswamy, his encounter with assorted persons at different places, and the agonies and anguishes of his life, Rao takes his readers on the august mission of life. Ramaswamy, the protagonist of the novel, comes to the realization that it is mere absurdity to live in human form if one does not have the urge for the Absolute. Therefore, he decides to stop life and look into it. He casts away all material achievements of life and submerges himself in the spiritual world, meditating upon if the world we live in is real or unreal - the serpent or the rope. The objective of the paper is to analyze the novel in terms of its hero’s quest for the Absolute, the path undertaken by him to reach the goal, and finally his realization of the Absolute. For this purpose, the study heavily draws upon various Tantric philosophical traditions as a tool to interpret the text.